Improving Communication and Motor Development Through Sports: A Systematic Literature Review - Riyan jaya Sumantri; Kartika Eka Eka Pertiwi; Fitria Hani Aprina; Dita Purnama; Yuning Eka Rahma Wati (International Journal on Advanced Science, Education, and Religion, 2026)
Communication is one of the most important aspects of human life. Without communication, interaction would not occur. Growth and development in early childhood are crucial because during this period—particularly between 0 and 12 months of age—children experience rapid growth and development. The purpose of this study is to determine the benefits of communication and motor development in enhancing physical activity based on a systematic literature review. The study employed the Systematic Literature Review (SLR) method. The database used to search for literature was Google Scholar. The results were presented by evaluating the quality of the documents in detail and in accordance with the scope of the study. Six relevant articles were identified out of 25 related articles. Based on search results aligned with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, engaging in physical activity can improve mental health. The documents sought in this study were those published within the last 10 years in nationally indexed Sinta journals and available as open access. Based on the results and discussion, the conclusion of this study states that exercise can improve motor development and communication.